Revaskularisasi Stenosis Saphenous Vein Graft (SVG) dengan Intervensi Koroner Perkutan (PCI): Laporan Kasus - Amalia Nurjanah; Wynne Putradana; Djoen Herdianto (Cermin Dunia Kedokteran, 2024)
Coronary artery bypass grafting (CABG) is the most ideal and frequently performed procedure for multi-vascular coronary artery stenosis, but its long-term prognosis is unfavorable. A 64-year-old male with a history of coronary artery graft surgery seven years ago complained of recurrent chest pain radiating to the jaw, relieved by isosorbide dinitrate. Physical examination, electrocardiography, and echocardiography test results were within normal limits. Laboratory results showed critical blood urea nitrogen (BUN) values requiring hemodialysis, on angiographic examination showed stenosis in all grafted and native coronary arteries. The diagnoses were grade III coronary artery disease and renal failure. Percutaneous coronary intervention using a drug-eluting stent (DES) in the saphenous vein graft conduit of the right coronary artery was performed, along with dual antiplatelet agents, b-blockers, nitrates, and statins.